2010
DOI: 10.1103/physrevb.82.184506
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic phase diagram ofFe(Se0.5Te0.5)single crystals in fields up to 28 tesla

Abstract: We report on specific heat ͑C p ͒, transport, Hall probe, and penetration depth measurements performed on Fe͑Se 0.5 Te 0.5 ͒ single crystals ͑T c ϳ 14 K͒. The thermodynamic upper critical field H c2 lines has been deduced from C p measurements up to 28 T for both H ʈ c and H ʈ ab, and compared to the lines deduced from transport measurements ͑up to 55 T in pulsed magnetic fields͒. We show that this thermodynamic H c2 line presents a very strong downward curvature for T → T c which is not visible in transport m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
97
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(127 citation statements)
references
References 60 publications
27
97
3
Order By: Relevance
“…Moreover, It has been reported that the zero temperature upper critical field of disordered superconductor shows deviation from the conventional one band WHH model and the observed values of H C2 (0) are smaller than the estimated values from conventional WHH model. [31][32][33][34][35][36][37][38] Similar deviation is also expected in our measurements. The broadening of the superconducting transition width in applied magnetic field is strongly related to the thermally activated flux flow mechanism.…”
Section: Resultssupporting
confidence: 76%
“…Moreover, It has been reported that the zero temperature upper critical field of disordered superconductor shows deviation from the conventional one band WHH model and the observed values of H C2 (0) are smaller than the estimated values from conventional WHH model. [31][32][33][34][35][36][37][38] Similar deviation is also expected in our measurements. The broadening of the superconducting transition width in applied magnetic field is strongly related to the thermally activated flux flow mechanism.…”
Section: Resultssupporting
confidence: 76%
“…[23][24][25][26]29 Muon spin rotation (µSR) measurements in FeSe x are consistent with either anisotropic s-wave or a two-gap extended s-wave pairing. 23 Microwave cavity perturbation technique determined both real and imaginary parts of the com- Table I plex impedance and, in addition to λ(T ), could also estimate temperature -dependent scattering time from which a crossover from dirty to a clean limit upon cooling has been proposed.…”
mentioning
confidence: 64%
“…2(e)] we find a decay length of ξ = 1.30 nm, in good agreement with the coherence length obtained from H c2 of 1.5 nm. 23 …”
Section: Spatial Inhomogeneity Of the Chemical Composition And Smentioning
confidence: 99%